Otimização do processo fermentativo de Bacillus subtilis no biocontrole de Sclerotinia sclerotiorum - Ruschel, Latoya Creslem Batista (2024)
Brazil is a leader in grain production, however, as it is a tropical country, it presents a greater pressure of diseases in its agricultural crops, such as white mold, caused by Sclerotinia sclerotiorum. This phytopathogen is difficult to control but can be managed with the use of Bacillus subtilis. Therefore, the present work aimed to optimize a fermentative process of B. subtilis focusing on the biocontrol of Sclerotinia sclerotiorum. The optimization was carried out based on a 3x3x3 factorial scheme, in which different temperatures (25, 30 and 35°C), different initial pHs (6, 6.5 and 7) and different agitation levels (100, 150 and 200 rpm) were evaluated in the bench fermentation process. The recurrent cell concentration of each assay was directly compared by the plaque antagonism method with S. sclerotiorum. From this pairing, 5 combinations with the greatest biocontrol potential were selected, which were evaluated for suppression of mycelial growth and sclerotia germination against volatile and diffusible organic compounds synthesized by B.subtilis. Furthermore, fermentative parameters were studied, such as the growth curve, maximum specific speed, generation time and cell concentration. Of the 5 combinations, the one with the greatest control potential was selected in order to verify the efficiency in the field regarding mycelial and carpogenic germination of sclerotia, as well as the shelf life when stored at 16 °C. Optimization of fermentative parameters revealed the combination (35°C, pH 7 and 100 rpm) as the one that maximizes biocontrol, providing 76.66% control of mycelial growth. Furthermore, it was found that volatile compounds are more efficient than diffusible compounds in sclerotia germination. Cell concentration and endospore formation reached expectations, as did the shelf life of the selected assay, in which cell viability was maintained for at least 40 days. Assay 21 was efficient for mycelial inhibition of sclerotia in the field (35%) and in reducing carpogenic germination with 50.25% of non-viable sclerotia.